Effect of COVID-19 lockdown on bovine economy in Uttar Pradesh - DUBEY, S K; SINGH, ATAR; SINGH, A K; PANDEY, SADHNA; SINGH, RAGHWENDRA; PANDE, AMAN Y KUMAR; SINGH, RAJEEV (The Indian Journal of Animal Sciences, 2021)
A study was conducted among 570 farmers spread across 57 districts (out of 75) of Uttar Pradesh from 10 April to 10 May 2020 by telephonic contact using the pre-structured interview schedule to assess the impact of CoVID 19 lockdown on the investment and profitability of major bovines of the state namely cattle and buffalo each with 460 data points. Different indicators for research variables namely investment pattern and profitability were measured by asking direct questions to the randomly selected 10 farmers from each district during the lockdown period and their experiences during last year (2019). The collected data were subjected for descriptive analysis - average, percentage, rank, standard deviation (SD) and coefficient of variation (CV), and also to the paired t-test to see the significance of difference, if any. Findings of the study showed that all the investments indicators like feed and fodder price, treatment cost, animal handling charges and total cost of milk production of cattle and buffalo enhanced significantly during the lockdown. The magnitude varied as per the nature of the cost components. The price variation was observed across the sample respondents and district. Similarly, for profitability indicators, there was reduction in the magnitude of milk sale (13-15%), selling price of milk (4-5%) and B:C ratio (5.2 -7.3%) significantly owing to lockdown. The perceptions of KVK experts from across the selected districts were also analyzed. During this period, KVKs of the state also disseminated various advisories, instructions, crop and enterprise-specific recommendations.